Generasi Berencana Peduli Organ Reproduksi Perempuan (GenRe POP) Dalam Meningkatkan Personal Menstrual Hygiene Pada Remaja - Veronica Yeni Rahmawati; Jehan Puspasari; Ernawati E; Casman C; Mellyani Eka Sari; Rici Rianjar (PT.Mantaya Idea Batara, 2021)
Adolescents are at risk of health problems, especially when they face signs of adolescent development during puberty, namely menstruation. Adolescents tend to be less likely to maintain personal hygiene during menstruation (personal menstrual hygiene). Improper behavior in personal menstrual hygiene in adolescents can cause reproductive tract infections and other health problems. The purpose of this activity is to increase the knowledge and insight of adolescents in general to maintain personal hygiene during menstruation. The method of this activity is divided into several steps, starting with the socialization of the activity agenda, providing educational materials to teenagers through Zoom meetings, edutainment of the snake and ladder game on the carpet in the courtyard of the mosque area and finally a discussion (FGD) for mothers of teenagers about personal menstrual hygiene. The result of this activity is an increase in knowledge of personal menstrual hygiene in adolescents before and after attending education. Providing education that is packaged with a snake and ladder game model is proven to be effective in increasing adolescent knowledge about personal menstrual hygiene.